OP0026 A PHASE 3 STUDY OF THE EFFICACY AND SAFETY OF PEFICITINIB (ASP015K) IN PATIENTS WITH RHEUMATOID ARTHRITIS WHO HAD AN INADEQUATE RESPONSE TO METHOTREXATE. (June 2019) - Takeuchi, Tsutomu; Tanaka, Yoshiya; Tanaka, Sakae; Kawakami, Atsushi; Iwasaki, Manabu; Rokuda, Mitsuhiro; Izutsu, Hiroyuki; Ushijima, Satoshi; Kaneko, Yuichiro; Shiomi, Teruaki; Yamada, Emi
Abstract : Background: Peficitinib (ASP015K), a novel oral JAK inhibitor, demonstrated efficacy as once-daily monotherapy in patients with moderate-to-severe rheumatoid arthritis (RA) in a phase 2b study (NCT01649999 ) 1 . Objectives: To evaluate the efficacy and safety of peficitinib–methotrexate (MTX) combination in patients with RA who had an inadequate response to MTX. Methods: This multicentre, randomised, double-blind, parallel-group, placebo (PBO)-controlled, phase 3 study (NCT02305849 ) was conducted in Japan. Patients had RA diagnosed within the past 10 years (1987 ACR or 2010 ACR/EULAR criteria), active disease (≥6 tender and painful joints and ≥6 swollen joints, using 68 and 66-joint assessment respectively; CRP ≥1.0 mg/dL; bone erosion; and ACPA or RF positivity) and inadequate response to MTX (administered for ≥90 days; ≥8 mg/week for ≥28 days prior to baseline). Patients were randomised 1:1:1 to 52-week MTX plus PBO, peficitinib 100 mg/day or peficitinib 150 mg/day. At week 12, inadequate responders in the PBO group (<20% improvement from baseline in tender and swollen joint counts) were switched (under blinded conditions) to peficitinib 100/150 mg until end of treatment. Remaining patients in the PBO group were switched (under blinded conditions) to peficitinib at week 28. Concomitant stable MTX dose (≤16 mg/week) was mandatory. Primary efficacy variables were ACR20 response rate at week 12/early termination (ET) and change from baseline in modified Total Sharp score (mTSS) at week 28/ET. Results: 519 patients were treated: PBO (n=170), peficitinib 100 mg (n=175) and peficitinib 150 mg (n=174). At week 12, 75 PBO-treated patients were switched to peficitinib 100 mg (n=37) and 150 mg (n=38) due to inadequate response. At week 12/ET, peficitinib showed superior efficacy vs PBO with respect to symptoms and inflammatory markers (Table 1 ). At weeks 28 and 52, peficitinib significantly reduced the mean mTSS change from baseline vs PBO (Table 1 ). Week 0–12 safety results were similar for PBO and peficitinib (Table 2 ). For the overall study period, incidence rate of serious infections per 100 patient-years was higher with peficitinib 100 mg/150 mg than PBO (Table 2 ). Conclusion: In patients with RA who had an inadequate response to MTX, peficitinib 100 mg/day and 150 mg/day demonstrated significant superiority vs PBO in reducing RA symptoms and suppressing joint destruction, according to primary efficacy variables (ACR response and change in mTSS). Peficitinib 100 mg and 150 mg showed acceptable safety and tolerability, with no new safety signals compared with other JAK inhibitors. Reference: [1] Takeuchi T, et al. Ann Rheum Dis2016; 75: 1057–64 Acknowledgement: This study was sponsored by Astellas Pharma, Inc. Medical writing support was provided by Rhian Harper Owen of Cello Health MedErgy and funded by Astellas Pharma, Inc. Disclosure of Interests: Tsutomu Takeuchi Grant/research support from: Astellas Pharma Inc, Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co., Ltd., Takeda Pharmaceutical Co., Ltd., AbbVie GK, Asahikasei Pharma Corp., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Eisai Co., Ltd., AYUMI Pharmaceutical Corporation, Nipponkayaku Co. Ltd., Novartis Pharma K.K., Grant/research support from: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Grant/research support from: Astellas Pharma Inc., Bristol Myers Squibb, Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahi Kasei Pharma Corp., Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Janssen Pharmaceutical K.K., Celltrion Inc., Nipponkayaku Co. Ltd., and UCB Japan, Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., Abbivie GK, Nipponkayaku Co.Ltd, Janssen Pharmaceutical K.K., Astellas Pharma Inc., Taiho Pharmaceutical Co. Ltd., Chugai Pharmaceutical Co. Ltd., Taisho Toyama Pharmaceutical Co. Ltd., GlaxoSmithKline K.K., UCB Japan Co. Ltd., Consultant for: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., Asahi Kasei Medical K.K., AbbVie GK, Daiichi Sankyo Co., Ltd., Bristol Myers Squibb, and Nipponkayaku Co. Ltd., Speakers bureau: Astellas Pharma Inc., Bristol Myers Squibb, Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahi Kasei Pharma Corp., Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Janssen Pharmaceutical K.K., Celltrion Inc., Nipponkayaku Co. Ltd., and UCB Japan, Speakers bureau: AbbVie, Asahi Kasei, Astellas, AstraZeneca, AYUMI, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Eli Lilly Japan, Janssen, Mitsubishi Tanabe, Nippon Kayaku, Novartis, Pfizer Japan Inc, Taiho, Taisho Toyama, Takeda, Teijin, Speakers bureau: AbbVie GK., Bristol–Myers K.K., Chugai Pharmaceutical Co. Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Astellas Pharma Inc, Diaichi Sankyo Co. Ltd., Eisai Co. Ltd., Sanofi K.K., Teijin Pharma Ltd., Takeda Pharmaceutical Co. Ltd., Novartis Pharma K.K., Yoshiya Tanaka Grant/research support from: Abbvie, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eisai, Mitsubishi-Tanabe, MSD, Ono, Taisho-Toyama, Takeda, Speakers bureau: Abbvie, Asahi-kasei, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eli Lilly, Eisai, Glaxo-Smithkline, Janssen, Mitsubishi-Tanabe, Novartis, Pfizer Japan Inc, Sanofi, Takeda, UCB, YL Biologics, Sakae Tanaka Grant/research support from: KYOCERA Corporation and Asahi Kasei Corporation, Consultant for: Amgen Astellas BioPharma K.K., KYOCERA Corporation, Pfizer and Daiichi Sankyo Co., Ltd., Speakers bureau: Asahi Kasei Corporation, Astellas Pharma Inc, Ayumi Pharmaceutical Corporation, Eisai Co., Ltd., Ono Pharmaceutical Co., Ltd., Daiichi Sankyo Co., Ltd, Taisho Toyama Pharmaceutical Co., Ltd., Mitsubishi Tanabe pharma Corporation, Chugai Pharmaceutical Co., Ltd., Teijin Pharma Ltd., Eli Lilly, Hisamitsu Pharmaceutical Co, Inc., Pfizer, Bristol-Myers., Atsushi Kawakami Grant/research support from: Astellas Pharma, Consultant for: Astellas Pharma, Speakers bureau: Astellas Pharma, Manabu Iwasaki: None declared, Mitsuhiro Rokuda Employee of: Astellas Pharma, Inc., Hiroyuki Izutsu Employee of: Astellas Pharma, Inc., Satoshi Ushijima Employee of: Astellas Pharma, Inc., Yuichiro Kaneko Employee of: Astellas Pharma, Inc., Teruaki Shiomi Employee of: Astellas Pharma, Inc., Emi Yamada Employee of: Astellas Pharma, Inc.